Price stability and monetary policies in Turkey - Tasak, İdris (My University, 2009)
PRICE STABILITY AND MONETARY POLICIES IN TURKEY The ongoing turmoil that began in U.S. in financial markets due to a loss of information about the location and size of the risk resulted in a global crisis. Main actors were the Sub-prime borrowers and lenders. Uniquely desinged sub-prime mortgages interwined with the complex financial innovations, although provided home ownership opportunities to riskier borrowers brought the global economy on the edge of the millennium’s first crash. In this study the complicated financial products and their relation to the sub-prime mortgages are detailly analyzed.

TÜRKİYE’DE FİYAT İSTİKRARI VE PARA POLİTİKASI A.B.D. finans piyasalarında başlayan panik barındırdığı riskin yeri ve boyutları konusunda yeterli bilginin olmaması nedeniyle küresel krize dönüşmüştür. Alt gelir grubuna kredi veren finans kuruluşuna ve alt gelir grubuna mensup kredi kullanıcıları krizin başlıca aktörleriydi. Özel olarak dizayn edilmiş sub-prime mortgage ürünleri karmaşık finansal süreçlerle bir araya gelerek, küresel finans piyasalarını milenyumun ilk büyük krizinin içerisine atmıştır. Bu çalışmada, karmaşık finansal ürünler ve bunların sub-prime mortgage piyasasıyla ilişkisi ayrıntılı olarak incelenmiştir.
Keywords: Para Politikası_Türkiye